Ex vivo live cell tracking in kidney organoids using light sheet fluorescence microscopy - Marie Held (University of Dundee, 2017)
We have adapted the mouse kidney rudiment assay to generate renal organoids. To demonstrate that the organoid culture method of re-aggregated kidney rudiments in PDMS discs resulted in 3D kidney organoids with organotypic structures, we stained fixed six day old organoids for various developmental markers and imaged them with a light sheet fluorescent microscope. We have stained for the following markers: Megalin, Laminin, Cytokeratin, Pax2, Six2, Wt1, Synaptopodin and Nephrin and have also used the lectin stain PNA (peanut agglutinin). The spheroids were usually imaged as z stacks from five angles.
Keywords: Renal re-aggregation, organoid, light sheet fluorescence microscopy, nephron, differentiation, glomeruli, podocytes, live imaging, cell tracking